The centralized hazardous gas detector system using microcontroller / Ishak Annuar and A. M Omar - Annuar, Ishak; Omar, A. M (2006)
A new approach to centralized hazardous gas detectors using a low cost embedded microcontroller system is presented. Particularly emphasized is the innovation of an auto RS232 to RS485 converter using PIC16F877 Supported devices that included embedded system, external devices and problem related with multi drop communication were briefly discussed. The operation of the system is monitored using Graphical User Interface (GUI) developed based on QBasic environment. The complete prototype system was developed and the performance is reported in this paper.